Prediction of The High Voltage Insulators Service Life Based on The Effective Values of Leakage Currents - Iosef Breido; Valeriy Ivanov (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The insulation condition of overhead lines is one of the main factors affecting reliability of overhead power transmission lines. It is known that the process of insulation lapping or rupture is mainly affected by environmental conditions and the degree of pollution of the insulators surface. This paper substantiates the possibility of using the leakage current values of insulators for monitoring the state of insulation and predicting its resource. The results of experimental studies of leakage currents of high-voltage insulators depending on their service life are given, on the basis of which forecasting the possible resource of insulators is carried out. The results obtained can be used to develop more effective diagnostics for detecting insulator failures at an early stage to take appropriate measures to coordinate the insulation.